Pengaruh Sikap Kewirausahaan Terhadap Minat Berwirausaha Siswa Dalam Mengelola Teaching Factory di SMK Negeri 1 Singaraja - Pratiwi, Gusti Ayu Made Dwi; Suwendra, I Wayan (Jurnal Pendidikan Ekonomi Undiksha, 2024)
This study aims to determine (1) the effect of entrepreneurial attitudes on students' interest in entrepreneurship in managing teaching factories at SMK Negeri 1 Singaraja. (2) How much influence does an entrepreneurial attitude have on students' entrepreneurial interest in managing the teaching factory at SMK Negeri 1 Singaraja? This research was conducted at SMK Negeri 1 Singaraja, with a total sample of 83 students from the acquisition of the Slovin formula. The sampling technique used in this study is probability sampling. This type of research is causality research with a quantitative approach and data collection methods using questionnaires and analyzed using descriptive analysis and simple linear regression analysis.The results of this study are that it is known that the attitude variable (X) has a significance value of 0.000 < 0.05, so that attitudes have a positive and significant effect on students' interest in entrepreneurship at SMK N 1 Singaraja. Judging from the magnitude of the influence, the magnitude of the coefficient of determination (R Square) 0.878 is equal to 87%.This means that the entrepreneurial attitude variable affects the interest in entrepreneurship variable by 87%, and the rest is influenced by other variables not examined in this study.